Stability of Foams and Froths in the Presence of Ionic and Non-Ionic Surfactants - R-H Yoon (The Australasian Institute of Mining and Metallurgy, 2005)
The thin film pressure balance (TFPB) technique was used to measure the kinetics of thinning of single foam films and disjoining pressures in the presence of sodium dodecyl sulfate (SDS) and electrolyte (NaCl). The results were analysed in view of the Reynolds equation to determine the role of surface forces in film thinning. It was found that film thinning is controlled by surface forces at thicknesses below approximately 200 nm. It was also found that hydrophobic force plays an important role particularly at low SDS and NaCl concentrations. The values of the hydrophobic force constant (K232) estimated from the film thinning experiments were used to predict the disjoining pressure isotherm using the extended DLVO theory, which were found to be in excellent agreement with experiment. The TFPB technique was also used to measure the equilibrium thicknesses (He) of the foam films stabilised by a non-ionic surfactant, n-octanol, in the presence of NaCl. At a given ionic strength, He increased noticeably with increasing octanol concentration at very low concentrations. This observation suggests that hydrophobic force is at its maximum level in the absence of surfactant and decreases with increasing surfactant concentration. The results obtained with the single foam films were used to explain the stability of the three-dimensional foams.